2015
DOI: 10.1095/biolreprod.115.128298
|View full text |Cite
|
Sign up to set email alerts
|

RBBP4 Regulates Histone Deacetylation and Bipolar Spindle Assembly During Oocyte Maturation in the Mouse1

Abstract: During meiosis I (MI) in oocytes, the maturation-associated decrease of histone acetylation is critical for normal meiotic progression and accurate chromosome segregation. RBBP4 is a component of several different histone deacetylase containing chromatin-remodeling complexes, but RBBP4's role in regulating MI is not known. Depleting RBBP4 in mouse oocytes resulted in multipolar spindles at metaphase (Met) I with subsequent perturbed meiotic progression and increased incidence of abnormal spindles, chromosome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Histone deacetylation may be sensitive to exogenous factors such as excessive follicle stimulating hormone or stress, which can also induce oocyte aneuploidy (Roberts et al, 2005; Salvador et al, 2001; Xu et al, 2011). The histone deacetylases: HDAC1, HDAC2, HDAC3, RBBP4, RBBP7, and Haspin are implicated in histone deacetylation in oocytes (Balboula et al, 2014; Balboula, Stein, Schultz, & Schindler, 2015; De La Fuente, 2014; Eot‐Houllier, Fulcrand, Watanabe, Magnaghi‐Jaulin, & Jaulin, 2008; Ma & Schultz, 2013; Q. Wang et al, 2006). One study in porcine oocytes found that class I HDACs in the germinal vesicle were not responsible for global deacetylation, and that instead other cytoplasmic HDACs were responsible (Endo, Kano, & Naito, 2008).…”
Section: Oocyte Histones and Histone Modifiersmentioning
confidence: 99%
“…Histone deacetylation may be sensitive to exogenous factors such as excessive follicle stimulating hormone or stress, which can also induce oocyte aneuploidy (Roberts et al, 2005; Salvador et al, 2001; Xu et al, 2011). The histone deacetylases: HDAC1, HDAC2, HDAC3, RBBP4, RBBP7, and Haspin are implicated in histone deacetylation in oocytes (Balboula et al, 2014; Balboula, Stein, Schultz, & Schindler, 2015; De La Fuente, 2014; Eot‐Houllier, Fulcrand, Watanabe, Magnaghi‐Jaulin, & Jaulin, 2008; Ma & Schultz, 2013; Q. Wang et al, 2006). One study in porcine oocytes found that class I HDACs in the germinal vesicle were not responsible for global deacetylation, and that instead other cytoplasmic HDACs were responsible (Endo, Kano, & Naito, 2008).…”
Section: Oocyte Histones and Histone Modifiersmentioning
confidence: 99%
“…In some cancer cell lines, AURKC localizes to centrosomes (Dutertre et al, 2005;Khan et al, 2011), and overexpression of AURKC can rescue multipolar spindle formation in RBBP4 and RBBP7-depleted oocytes (Balboula et al, , 2015. Because we know that haspin regulates AURKC chromosomal localization (Nguyen et al, 2014), we re-evaluated AURKC and haspin localization.…”
Section: Haspin Activity Is Required For Aurkc Localization At Mtocsmentioning
confidence: 99%
“…Previous scientific research demonstrated that RBBP4 can regulate HDAC and also participate in the process of RBBP4 protein by phosphorylation and dephosphorylation during oocyte meiotic maturation in mice (Balboula et al, 2015). The decrease of RBBP4 has been shown to influence the formation of spindle body and chromosome dislocation in M1 (Balboula et al, 2015), and later studies of this protein in planarians revealed that it can control the expression of the requisite genes in cellular differentiation through affecting the structure of chromatin (Bonuccelli et al, 2010). In this study, the As-RBBP4 protein was predicted to have neither a signal peptide nor transmembrane domain, indicating that it is not a secreted or transmembrane protein.…”
Section: Discussionmentioning
confidence: 99%